Lumbar Erector Spinae Plane Block for Total Hip Arthroplasty Comparing 24-Hour Opioid Requirements: A Randomized Controlled Study - Dahlia Townsend; Nasir Siddique; Atsumi Kimura; Yaacov Chein; Eli Kamara; John Pope; Mitchell Weiser; Singh Nair; Iyabo Muse (Anesthesiology Research and Practice)
Study Objective. Neuraxial and regional anesthesia have become commonly utilized for patients undergoing total hip arthroplasty to aid in postoperative analgesia, facilitating early ambulation and better functional recovery. This study investigated the efficacy of a lumbar erector spinae plane block (ESPB) on reducing postoperative opioid consumption in total hip arthroplasty performed under spinal anesthesia. Design. Prospective, randomized, controlled trial. Patients. Sixty-three adult patients with an American Society of Anesthesiologists Status I–III who are undergoing elective primary total hip arthroplasty. Interventions. Patients were randomized to the control group (no block) or the ESPB group (preoperative ultrasound-guided lumbar ESPB). Intraoperatively, all patients received spinal anesthesia with moderate sedation. Postoperatively, patients received a standardized multimodal analgesia protocol. Measurements. The primary outcome was cumulative opioid consumption at 24 hours postoperatively. Secondary outcomes included cumulative opioid consumption at 8 hours and through 48 hours postoperatively and pain scores at 24 and 48 hours post surgery. Main Results. Thirty-one patients were randomized to the control group (spinal alone) and 32 patients to the ESPB group. The median opioid requirement in the first 8 hours after surgery was higher in the control group (28 mg of oral morphine equivalents (OME) versus 5 mg of OME in the ESPB group) (p=0.013). There was no statistically significant difference in opioid consumption between the groups at 24 hours (p=0.153) or 48 hours (p=0.357) postoperatively. There was no statistically significant difference in pain scores between the two groups through 24 hours (p=0.143) or 48 hours (p=0.617) after surgery. Conclusion. Lumbar ESPB reduces opioid utilization during the first 8 hours postoperatively after total hip arthroplasty but not thereafter. Evaluating the use of either adding a local anesthetic adjunct to the ESPB or using longer-acting local anesthetic warrants further investigation.